Molecular screening for Blastocystìs sp. in canine faecal samples in Greece - SPANAKOS (Γ. ΣΠΑΝΑΚΟΣ), G.; PAPADOGIANNAKIS (Ε. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ), E.; KONTOS (Β. ΚΟΝΤΟΣ), V.; MENOUNOS (Π. ΜΕΝΟΥΝΟΣ), P.; VELONAKIS (Ε. ΒΕΛΟΝΑΚΗΣ), E.; KOUTIS (Χ. ΚΟΥΤΗΣ), C.; VAKALIS (Ν. ΒΑΚΑΛΗΣ), N. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Blastocystìs is an anaerobic parasitic microorganism which has been found in the intestinal tract of many vertebrates including humans and dogs. Recently, members of Blastocystìs sp. were classified into nine sub-types, based on phylogenetic trees derived from sequence analysis of the small sub-unit ribosomal RNA gene. The pathogenesis of Blastocystìs in the dog remains uncertain and the existence of pathogenic and non-pathogenic sub-types is under investigation. Feacal samples from 30 privately owned and 42 stray dogs, originated from central and northern Greece, were examined by both light microscopy and PCR assays for the detection of Blastocystìs sp. All samples were found to be negative by both assays. It seems that, in Greece, the dog is unlikely to be a "reservoir" of Blastocystìs sp., although a large scale epidemiologic study is needed to be carried out in order for more conclusive results to be drawn.